Kepuasan Kerja Karyawan Biro Administrasi Akademik (BAA) Universitas Muhammadiyah Surakarta - Alamanda, Karina Putri, Dr. Moordiningsih, M.Si, Psi, Rini Lestari, S.Psi, M.Si., Psikolog (2016)
Employee satisfaction was an important issue that will affect the performance and achievement all over organizational objectives. The purpose of this study was to: (1) determine the condition and level of job satisfaction of the academic employee, (2) explore the factors that affect job satisfaction, (3) apprehend the psychological dynamic of job satisfaction and (4) develop a program that can be applied to improve job satisfaction of the academic employee. This mixed methods study, collect data with MSQ (Minnesota Satisfaction Questionnaire) as quantitative data, an interview and observation as qualitative data. Purposive sample was use to determine the subject (7 employee), which represents the high, average and low category of job satisfaction. The results showed that (1) academic administration employee's job satisfaction was on average category which is able to be active and had a capable leader on manage co-worker , (2) work-itself, leader, co-workers, advancement, salary, working condition, customer satisfaction, and individual values was the factor which influence job satisfaction, (3) psychological dynamic of job satisfaction was described by fulfilled or given chance to fulfill the intrinsic aspects (Activity, Social service, Ability utilization, Social status) and extrinsic aspects (Company policies and practice, Supervision-technical, Advancement, Recognition) of satisfaction and the importance factors of satisfaction by employee which affect their satisfaction. When the importance aspects and factors fulfilled then employee will be satisfied. Further job satisfaction expressed by given aspiration, loyalty, exit and neglect, (4) persuasion, openness, and empathy's skills of communication was needed by the employee to support job changed and develop relation between leader and employee, so interpersonal communication training was the recommendation program for increase job satisfaction. Pay attention of employee satisfaction and maintaining it, become one of focus of institute for achieve organizational objectives.